John Maxwell Freeland interviewed by Hazel de Berg in the Hazel de Berg collection - Freeland, J. M. (John Maxwell), 1920-1983.; De Berg, Hazel, 1913-1984. (1971)
Freeland speaks of his family background; studying on the repatriation opportunities for ex-servicemen; lecturing in architecture at the University of N.S.W. (1957); the history of the school of architecture at the University of N.S.W.; his interest in Australian and architectural history; his concern for architectural heritage.
Also available online
Transcript available (17 p.)
Keywords: Freeland, J. M. -- 1920-1983 -- Interviews; University of New South Wales. -- School of Architecture; Architects -- Australia -- Interviews; College teachers -- Australia -- Interviews